RANCANG BANGUN SISTEM INFORMASI PORTAL BERITA BERBASIS WEB PADA DINAS PEMUDA DAN OLAHRAGA KABUPATEN CIREBON - Pratama, Hilda Fidyah Hadi; Hamonangan, Ryan; Herdiana, Ruli; Tohidi, Edi; Hayati, Umi (MEANS (Media Informasi Analisa dan Sistem), 2022)
The Cirebon Regency Youth and Sports Office (Dispora Cirebon) is a regional work unit that is given the mandate and duties and responsibilities in handling development in the Youth and Sports Sector in the Cirebon Regency environment. In this day and age, a touch of Information System technology such as a website must have become a necessity for government agencies, as a support for more centralized, accurate, and fast information. However, there was no website-based information system at the Cirebon Dispora as a medium for disseminating information at that time. The writer uses primary data sources (Observation and Interview) and secondary data sources (Documentation Study). For system design, the author uses the SDLC (System Development Life Cycle) method. The final result obtained is a website-based Information System, which can provide information about profiles, activities or articles about Dispora Cirebon to the wider community. With several advantages of website technology, the Website-Based News Portal Information System is expected to expand the reach of information dissemination to all aspects of society.